Photothermal solar assisted Madhuca diethyl ether fuel processing for LHR engines with AI-based performance and yield prediction - Rakesh Dubey; Ajeet Kumar Prajapati; Shruti Bharadwaj; Viroon Kamchoom; Kennedy C. Onyelowe; Krishna Prakash Arunachalam (Scientific Reports, 2026)
emissions. Heat release rate analysis indicated earlier and more efficient combustion behavior. Additionally, LSTM-based predictive modeling showed lower error margins compared with RNN, demonstrating improved prediction accuracy for engine performance parameters.
Keywords: Biodiesel Production and Applications; Solar Thermal and Photovoltaic Systems; Solar-Powered Water Purification Methods